Reliability, Learnability and Efficiency of Two Tools for Cement Crowns Retrieval in Dentistry - Bignardi, Cristina (Open Biomed Eng J, 2018)
BACKGROUND: Tooth-supported fixed dentures are commonly used in restorative dentistry, and have definitely reached a high survival rate; nevertheless, their removal is sometimes required mainly due to caries or other failures (poor fit, poor cementation and so on). Removing a definitive partial denture is not trivial since the used cement is not always known and it may be very resistant; additionally, there are various clinical circumstances in which a conservative disassembly would be desirable. OBJECTIVE: assessing the performance of different tools for cement crowns retrieval in terms of reliability, learnability and efficiency. METHODS: An experimental study has been performed on two different devices for conservative crown/bridge removal: a manual tool that is a sliding hammer, and an automatic tool, powered by compressed air. Both skilled and unexperienced operators have been considered and an experimental set up has been appositely designed in order to measure force versus time patterns. The peak applied force has been taken as an output variable for the evaluation of tool performance. RESULTS: The automatic tool improves both the inter-operator and the intra-operator reliability, respectively from 79% to 95%, and from 69% to 92%. Additionally, the force pattern is significantly different between these two tools: the instrument powered by compressed air, produces a sharper peak force, as required to break fragile materials such as dental crown cement, and its efficiency can be estimated to be 75% higher. Both tools have a high learnability since the performances of experienced and unexperienced operators have not proved to be significantly different. CONCLUSION: A methodology has been set up to compare tools for cement crowns retrieval. The compressed-air tool has been proved to generally provide a better performance unless more ductile cement is to be broken.